PERANCANGAN INTERIOR TOKO ELEKTRONIK DI SUKABUMI - Michelle Carolina; Stephanus P Honggowidjaja (Intra, 2018)
Electronic stores are generally known as a place for selling electronic appliances that are disorganized - in the sense that they are concerned only with the principle of sales and profits. This design aims to create an electronic store design with a holistic problem solving, from the commercial, function, and aesthetics side, which design is based on the real project that the author did professionally.Interior Design of Electronic Shop in Sukabumi is designed by creating a brand image in terms of creating characteristics of the store from interior design side as an initial design for development in the future as well as unifying the concept of the store so as to give the impression unity. In addition, a sustainable commercial interior approach is also used to create value in design. The design is also equipped with supporting facilities such as Sunda Café for leisure, commercial office room, service & trial area, information booth, credit booth, warehouse, loading dock area, and employee’s room.